2020
DOI: 10.1097/prs.0000000000006315
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Insurance Payer on Type of Breast Reconstruction Performed

Abstract: Background: The impact of insurance and socioeconomic status on breast reconstruction modalities when access to care is controlled is unknown. Methods: Records for patients who underwent breast reconstruction at an academic medical center between 2013 and 2017 were reviewed and analyzed using chi-square analysis and logistic regression. Results: One thousand six hundred eighty-three breast reconstructions we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 30 publications
2
26
1
Order By: Relevance
“…42 Of note, several studies have found racial and ethnic disparities in surgical access, outcomes, and costs, among other craniofacial surgeries. 2,9,41 One such study by Wu et al 2 found that minority patients had increased surgical costs of CLP repair. Variations in surgical costs are often influenced by differences in length of stay or complication rates.…”
Section: Influential Factors On Cost Of Surgerymentioning
confidence: 99%
“…42 Of note, several studies have found racial and ethnic disparities in surgical access, outcomes, and costs, among other craniofacial surgeries. 2,9,41 One such study by Wu et al 2 found that minority patients had increased surgical costs of CLP repair. Variations in surgical costs are often influenced by differences in length of stay or complication rates.…”
Section: Influential Factors On Cost Of Surgerymentioning
confidence: 99%
“…10–12 Of those patients who do undergo autologous reconstruction, the privately insured have been shown to receive free flap, rather than pedicled, reconstruction at significantly higher rates than those insured by Medicare or Medicaid. 8,10…”
Section: Introductionmentioning
confidence: 99%
“…6,7 It has been proposed that relatively low reimbursement rates from Medicare and Medicaid do not provide sufficient compensation for the increased procedural time and technical skill required for autologous reconstruction, thus disincentivizing utilization of autologous-based reconstruction and possibly accounting for the increasing rates of implant-based reconstruction nationally. 8,9 Previous research has identified a significant disparity in reconstructive modality, based on insurance status, race, and other sociodemographic characteristics. Nonminority, privately-insured women from advantageous socioeconomic backgrounds have been shown to receive autologous-based reconstruction at much higher rates than other breast cancer reconstruction patients.…”
Section: Introductionmentioning
confidence: 99%
“…29 In addition, Chouairi et al found that women with private insurance were more likely to undergo autologous reconstruction, but women with Medicaid and Medicare were more likely to undergo prosthetic reconstruction. 30 Although there is a paucity in the literature regarding the association of socioeconomic status and breast reconstruction readmissions, previous work has shown that income inequality is associated with higher readmission rates in heart failure, myocardial infarction, and pneumonia. 31 Readmission following lung lobectomies has also been found to be influenced by median household income and insurance status.…”
Section: Discussionmentioning
confidence: 99%